Lifelong Education: External and Internal Constructs of Human Motivation - O. P. Kurdenkova (Vestnik MGIMO-Universiteta)
Rapid changes in the modern society lead to the alteration of the role of education in it. Knowledge obtained several years ago becomes outdated and not relevant. Permanent development of one's skills and acquirement of new competences are the essential and integral part of a modern society. At the summit in Lisbon in 2000, lifelong education was defined as the priority in the development of educational policy within European Educational Area. Six major principles were also represented. Effective and sustained results of application of lifelong learning conception are closely connected with the implementation of these principles. The Russian Federation signed the Bologna Declaration in 2003. As a result active work on implementing the ideas of lifelong education is conducted. According to statistics, motivation towards continuation of education among the Russian population is extremely low. The author points to the importance of this problem, as motivation is the driving force of every activity. Analyzing European experience the author affirms that creation of the state educational policy based on lifelong learning is one of the key priorities. Active participation of the government will contribute to increase of the motivation towards continuation of education among all the age groups.